Concise synthesis of (+)-deoxoprosophylline via Co(III)(salen)-catalyzed two stereocentered HKR of racemic azido epoxides - Devalankar, Dattatray A.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
An efficient synthesis of (+)-deoxoprosophylline has been achieved in high optical purity (99% ee) from readily available cis-2-butene-1,4-diol. The strategy employs Co-catalyzed Hydrolytic Kinetic Resolution (HKR) of two stereocentered racemic azido epoxides and diastereoselective intramolecular reductive cyclization as key reactions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Azido epoxide; Hydrolytic kinetic resolution; Piperidine; Wittig olefination

Concise enantioselective syntheses of (+)-L-733,060 and (2S,3S)-3-hydroxypipecolicw acid by cobalt(III)(salen)-catalyzed two-stereocenter hydrolytic kinetic resolution of racemic azido epoxides - Devalankar, Dattatray A.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Synlett, 2014)
An efficient synthesis of the 2,3-disubstituted piperidines (+)-L-733,060 and (2S,3S)-3-hydroxypipecolic acid (99% ee) in high optical purity from commercially available starting materials is described. The strategy involves a cobalt-catalyzed hydrolytic kinetic resolution of a racemic azido epoxide with two stereocenters and an intramolecular reductive cyclization as key reactions.
Keywords: azides; cyclizations; epoxides; piperidines; stereoselective synthesis; Wittig reactions